Effects of Human Resource Management Practices on Organizational Commitment in Sri Lankan Public Sector Banks - Mangaleswaran, T.; Srinivasan, P.T. (AIMS Internal and University of Rajasthan, 2006)
HRM has tremendous relevance to service sector like Bank. Human input is the single largest input that contributes to improve productivity of the banking sector. This study was designed to explore the effect of HRM practices on organizational commitment in Srilankan Public Sector Banks. The sample was drawn from among 281 employees working in Public sector Banks in Sri Lanka. To measure the effect of HRM Practices on organizational commitment, a structured questionnaire was used to collect data. The results of this study reveal that the HRM practices influence the organizational commitment in Sri Lankan Public Sector Banks.